Women’s health: the new dimensions and homoeopathy of AYUSH - Tridibesh Tripathy; Shankar Das; Rakesh Dwivedi; Byomakesh Tripathy; Anjali Tripathy; Sanskriti Tripathy (International Journal Of Community Medicine And Public Health, 2026)
Women’s health is an integral part of public health and especially the reproductive health. The Reproductive and Child Health (RCH) is a big component in National Health Mission (NHM) where primarily the target is woman. This article discusses the span of women health across the various stages in the life of a woman. It traverses through the fact that reproductive health is not exclusively hormonal but also cellular. Here cellular means the mitochondria generated cellular energy. The cellular approach will help masses to see a variety of clinical conditions in women’s health but also understand the issues of ageing, fertility and vitality in women. With the new census coming up in 2027, almost half of the population or about 75 crores (750 million) will be women in India. It will also help policy makers to understand the complexity both clinically and culturally. It is a priority under the domain of Community Medicine and Public Health (CMPH). With the new view, health policies will be impacted and accordingly the women’s health approach has to be relooked. It clearly needs a holistic approach as the approaches till date were based on hormones. Future clinical approaches have to be preventive, resilient, cost effective, clinical effective and no side effects. Homoeopathy of AYUSH ministry of India has the quality to meet the future demands. NFHS 6 says that the menace of Non-Communicable Diseases (NCD) has surged. NCDs are the triggers in women’s health. Dealing with women’s health effectively means impacting future generations positively.